PERILAKU BODY SHAMING DALAM TINJAUAN HADIS NABI: Upaya Spritual sebagai Langkah Preventif atas Tindakan Body Shaming - M. Fahmi Azhar (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2022)
This article examines one of the social problems in society which is currently a global issue, namely body shaming behavior. Body shaming behavior is an act of commenting, criticizing or bullying someone's physical (body condition) with the aim of humiliating, because the physical condition of the individual is considered not in accordance with the applicable body image standards and deserves to be commented on. This study examines the behavior of body shaming from the perspective of the hadith. This study seeks to find a correlation between body shaming behavior and hadith, and explores the preventive actions offered by the Rasulullah. The method used is qualitative-descriptive through library research. The results of this study, 1). Hadith narrated by Tirmi>dhi> : 2502 in general explains how the prophet's view of body shaming behavior is. 2). The meaning of the hadith content in it is an invitation to stay away from body shaming behavior. 3). Impact on victims of body shaming behavior in a psychological perspective. 4). Preventive actions offered by the Rasulullah to prevent body shaming behavior.Artikel ini mengkaji salah satu permasalahan sosial di tengah masyarakat yang saat ini menjadi isu global, yaitu perilaku body shaming. Perilaku body shaming merupakan tindakan mengomentari, mencela, mengkritik atau merundung fisik (kondisi tubuh) seseorang dengan tujuan untuk mempermalukan, hal ini disebabkan kondisi fisik yang dimiliki individu tersebut dinilai tidak sesuai dengan standar citra tubuh yang berlaku dan layak untuk dipermalukan. Penelitian ini mengkaji perilaku body shaming perspektif hadis Nabi. Tulisan ini bertujuan untukÂ  menemukan korelasi antara perilaku body shaming dan hadis, serta mengeksplorasi tindakan preventif yang ditawarkan oleh Rasulullah. Metode yang digunakan adalah kualitatif-deskriptif melalui studi kepustakaan (library research). Hasil atas kajian ini, 1). Hadis riwayat Tirmi>dhi>: 2502 secara umum menjelaskan bagaimana pandangan nabi terhadap perilaku body shaming. 2). Pemaknaan kandungan hadis di dalamnya ajakan untuk menjauhi perilaku body shaming. 3). Dampak bagi korban perilaku body shaming dalam sudut pandang psikologi. 4. Tindakan preventif yang ditawarkan untuk mencegah perilaku body shaming.